METHODOLOGICAL AND TECHNOLOGICAL FOUNDATIONS FOR INTEGRATING DIGITAL AND INFOTAINMENT TECHNOLOGIES IN THE DEVELOPMENT OF TUTORS’ MANAGEMENT ACTIVITY (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the mechanisms for integrating digital and infotainment technologies into the development of tutors’ management activity in higher education. Contemporary universities increasingly rely on digital systems, analytics, AI-supported tools, and interactive media to strengthen student support, personalize learning pathways, and improve institutional responsiveness. At the same time, infotainment-oriented approaches—such as gamification, multimedia visualization, interactive storytelling, and engaging communication formats—are gaining attention because they can increase learner engagement and improve the accessibility of academic support. The study argues that the integration of these two technological directions is not merely a technical matter, but a pedagogical-management process requiring conceptual coherence, methodological grounding, organizational readiness, and ethical regulation.